Semiotika untuk Memahami Makna Arsitektur Ragam Hias - Sri Sunarti; Ikaputra (ATRIUM: Jurnal Arsitektur, 2021)
Title: Semiotics to Comprehend The Change in The Meaning of An Ornament   Semiotics is the science of a sign that consists of the structure of the signifier and the signified.  As a medium of communication, a sign serves as a stand of something else or represents an expression message from the maker or owner to another party (interpretant) to be able to read.  (Peirce, 1986 as cited in Chandler, 2007).  Ornamental architecture is a work of art as a sign that is a medium of communication to viewers or related parties, which contains meaning that is not yet known or understood.  The unknown meaning is caused by several types (1. decoration of new creations; 2. historical breakdown; 3. transfer of context; 4. correction of meaning due to discrepancies).  Given that ornamental architecture is a sign of a grammatical "text", it is possible to interpret it using the same scientific approach of signs. Presumably, semiotics is deemed appropriate even though the results of the interpretation are not absolute. The accuracy and experience (object, location, specific time) of the sign interpretant greatly determine the result of the meaning of the sign, besides the influence of the possible socio-cultural, economic, political, religious, technological background factors, typical forms, masses and evaluators.  The success in interpreting the sign proportionally becomes a reference in behaving or acting or placing ornamental architecture more proportionally.  This is where the role of semiotics is very helpful in interpreting the sign of ornamental architecture as a basis for further action. Therefore, all things around that are signs related to our lives can always be treated appropriately.